GPMN-Edit: High-level and Goal-oriented Workﬂow Modeling - Jander, Kai; Lamersdorf, Winfried (Electronic Communications of the EASST, 2011)
Workﬂow modeling and tools for designing and editing workﬂows is an important part of business process automation. One of the challenges of workﬂow design has been the gap between business users and technical users. While technical users require detailed and formal models for execution, the focus for business users generally consists of more abstract and business-related aspects of the workﬂow such as the purpose of the workﬂow and business goals it derives from the business process. One approach aiming to address this gap are goal-oriented workﬂows which explicitly represent the business goals as part of the workﬂow semantic. This paper presents an approach and a tool called GPMN-Edit for modeling such goal-oriented workﬂows using the Goal-oriented Process Modeling Notation (GPMN). Furthermore, GPMN-Edit allows users to mask speciﬁc details of the workﬂow they consider irrelevant for the task at hand while still being able to continue changing the workﬂow.